2016
DOI: 10.1093/brain/awv403
|View full text |Cite
|
Sign up to set email alerts
|

GABA transmission via ATP-dependent K+channels regulates α-synuclein secretion in mouse striatum

Abstract: α-Synuclein is readily released in human and mouse brain parenchyma, even though the normal function of the secreted protein has not been yet elucidated. Under pathological conditions, such as in Parkinson's disease, pathologically relevant species of α-synuclein have been shown to propagate between neurons in a prion-like manner, although the mechanism by which α-synuclein transfer induces degeneration remains to be identified. Due to this evidence extracellular α-synuclein is now considered a critical target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 69 publications
2
62
0
Order By: Relevance
“…Mitochondrial dysfunction has been associated with alpha-synuclein aggregation and degeneration of the nigrostriatal projection (Mullin and Schapira, 2013). Interestingly, in both wild-type and alpha-synuclein overexpressing transgenic mice, a substantial amount-if not the majority-of physiological alpha-synuclein in the striatum is localized at corticostriatal glutamatergic terminals (Totterdell and Meredith, 2005;Taguchi et al, 2016;Emmanouilidou et al, 2016; Figures 2A and 2B). Conversely, virtually no alpha-synuclein is detected in the cell bodies of the output cortical layers V and VI (Taguchi et al, 2016), and, importantly, relatively little alpha-synclein is localized at thalamostriatal and nigrostriatal terminals (Emmanouilidou et al, 2016; Figure 2B).…”
Section: Cortical Control Of Striatal Dopamine Releasementioning
confidence: 99%
“…Mitochondrial dysfunction has been associated with alpha-synuclein aggregation and degeneration of the nigrostriatal projection (Mullin and Schapira, 2013). Interestingly, in both wild-type and alpha-synuclein overexpressing transgenic mice, a substantial amount-if not the majority-of physiological alpha-synuclein in the striatum is localized at corticostriatal glutamatergic terminals (Totterdell and Meredith, 2005;Taguchi et al, 2016;Emmanouilidou et al, 2016; Figures 2A and 2B). Conversely, virtually no alpha-synuclein is detected in the cell bodies of the output cortical layers V and VI (Taguchi et al, 2016), and, importantly, relatively little alpha-synclein is localized at thalamostriatal and nigrostriatal terminals (Emmanouilidou et al, 2016; Figure 2B).…”
Section: Cortical Control Of Striatal Dopamine Releasementioning
confidence: 99%
“…It is important to emphasize that underlying mechanisms differ depending on whether the α-synuclein is present as a monomer, oligomer or fibril. A recent in vivo study indicated that monomeric α-synuclein is released from nerve terminals in the striatum in a process that is potassium-dependent and regulated by presynaptic GABA receptors (65). Monomers of α-synuclein appear to readily translocate across cellular membranes in a temperature-insensitive manner (22).…”
Section: Cellular and Molecular Mechanisms Of α-Synuclein Intercellulmentioning
confidence: 99%
“…Such a regulatory cascade would be expected given the high organization complexity of the specific neuronal networks. Of note, since neuronal communication is orchestrated by neurotransmitter release, this work also suggested that neurotransmitters could play a significant role in α‐synuclein secretion in vivo . This would be of critical importance in neurodegenerative diseases, such as Parkinson's disease, where loss of dopamine dramatically alters the firing pattern of neurons that receive dopamine input in other brain areas including the striatum and the cortex .…”
Section: Exocytosis Of α‐Synuclein: Insights From Cell Culture and Anmentioning
confidence: 79%
“…Even though the association of α‐synuclein with SVs has been reported, it is still unclear how the protein reaches and is incorporated in the membrane of SVs. Most importantly, recent data indicated that SVs do not seem to be involved in the secretion of α‐synuclein .…”
Section: Exocytosis Of α‐Synuclein: Insights From Cell Culture and Anmentioning
confidence: 99%
See 1 more Smart Citation